Male familiarity and aggressive behavior: Two modulators of female Japanese quail social preferences - Pellegrini, Stefanía (2020)
Sexually experienced female quail that have observed an aggressive interaction between a pair of males prefer the less aggressive male, while females with no previous sexual experience prefer the aggressive one. Although those studies were developed in a setup where birds can only interact through a glass separation (no physical contact), social proximity was discussed in terms of reproductive preferences. Another factor that modulates the birds’ choice to interact with conspecifics is the familiarity with other birds. Herein we assessed whether female quail will differentially modulate their social interactions with known or unknown males after observing them taking a high vs. a low aggressive role in a male-male encounter (4 experimental group combinations). Birds were housed in male-female pairs during the rearing period and all females tested were sexually experienced. At 100 d of age, 2 males were tested during up to 2 hs in the presence of their 2 female partners that remained as audience behind a wire partition in two separated compartments (27 total interactions). After the male-male encounters, males were classified as either high or low aggressive. Then (24 hs), the female interactions with those males were individually evaluated during 2 hs in a novel environmental setup that combined the two males fitted with an individual physical barrier (IPB) on their back, the female with no IPB and gated partitions within the apparatus. Thus, only females can freely ambulate through the gates and visit all compartments. This novel social test allows females to choose between remaining separated from each of the 2 males that are restrained in opposite sides of the apparatus, or to enter their environment and physically interact with them. Differences in the time spent with or near each male and numbers of mating and aggressions were analyzed using mixed GLM. Females spent more time (P<0.003) near their known male partner than with the unknown male regardless of the male aggressiveness observed, suggesting that familiarity strongly favors female social reinstatement. However, females copulated equally (P=0.53) with both males regardless of the male familiarity or aggressiveness shown during male-male encounters. Finally, females behaved more aggressively than males and were even more aggressive towards the unknown males. Furthermore, females were more aggressive (P<0.001) towards males that were highly aggressive during the male-male interactions than towards the males that were less aggressive. Taken together, the observed female social behavior suggests that the time spent near a conspecific or the aggressiveness performed against them cannot be used as reliable indicators of sexual preference.